Isolation and Fractionation of Lignin from Sugar Cane Bagasse (Saccharum Officinarum L.) as an Antioxidant - Tresia Marbun, Shondang (Malikussaleh University, Aceh, Indonesia, 2025)
Bagasse is one of the solid wastes of the sugar cane industry, and it contains lignin fibre. Lignin from sugarcane bagasse is also known to have relatively high antioxidant activity. Sugarcane bagasse antioxidants can stabilize free radicals by completing free radicals’ lack of electrons and inhibiting chain reactions from forming free radicals. This type of research is laboratory experimental research (actual experiment design). In this research, lignin isolation and fractionation will be carried out from sugarcane bagasse to obtain lignin fractions with antioxidant activity. The percentage of lignin yield from this process is around 72.85%. The IR spectrum resulting from isolation from sugarcane bagasse has a typical absorption peak of aliphatic and aromatic –CH at a wave number of 2919.7/cm. The antioxidant activity of the lignin fraction from sugarcane bagasse was determined using the DPPH (1,1-diphenyl-2- picrylhydrazyl) free radical scavenging method using four solvents, namely ethyl acetate, acetone and methanol. Based on the level of antioxidant strength, the strength level is 50 powerful, 50-100 strong, 100-250 medium, 250-500 weak and 500 inactive; therefore, the results of testing the most potent antioxidant activity in the acetone fraction were found to be ??50 50, 6755 mg/L and weak antioxidant activity was found in the methanol fraction, the result was ??50 68.8503.